Varietal identification study of six wheat varieties using ISSR markers (Mongolian Journal of Agricultural Sciences, 2018)
The identification of cereal and horticultural varieties are important for registration and agricultural systems. The traditional way to variety identification is the recording of morphological characters using descriptors. But molecular markers may serve as a modern and suitable approach to variety identification such as ISSR. The objective of the study was to identify the 17 ISSR primers, 801~849, for varietal identification of six wheat varieties, Darkhan-34, Darkhan-166 (Arvin), Darkhan-131, Darkhan-144, Khalkhgol-1 and Tsogt. As a result of ISSR marker observation on varieties, Arvin can be identified with 817, Khalkhgol-1 with 817 and 827, Tsogt with 822, Darkhan-34 with 830, Darkhan-131 with 830 and 848 and Darkhan-144 with 827, 830 and 848 primers. Among the surveyed ISSR primers, five can be used as variety-specific primers, 817, 827, 822, 830 and 848.